Wstępne uwagi o normie składniowej aktów prawnych - Gębka-Wolak, Małgorzata (Poznańskie Spotkania Językoznawcze, 2014)
The article discusses the question of syntactic norm of legal acts on the background of the syntactic norm of the standard language. After the presentation of the relationship between the syntactic norm of legal acts and the norm of the standard language, especially its model variety, the author continues to describe the selected syntactic features testifying to a specific character of the observed norm. The examples given furnish evidence for quantitative and qualitative differences between the standard and the professional norm. Two research postulates can be put forward as a result of the conducted analyses. The first one, of general nature, concerns efforts which would be aimed at the new presentation of the position of the professional norm in the norm of the standard Polish language. The second postulate refers to the studies of the legal language which should be expanded by embracing the problems concerning the codification of a syntactic norm.